2020
DOI: 10.3389/fcell.2020.00839
|View full text |Cite|
|
Sign up to set email alerts
|

An MRTF-A–Sp1–PDE5 Axis Mediates Angiotensin-II-Induced Cardiomyocyte Hypertrophy

Abstract: Cardiac hypertrophy is a critical intermediate step in the pathogenesis of heart failure. A myriad of signaling networks converge on cardiomyocytes to elicit hypertrophic growth in response to various injurious stimuli. In the present study, we investigated the cardiomyocyte-specific role of myocardin-related transcription factor A (MRTF-A) in angiotensin-II (Ang-II)-induced cardiac hypertrophy and the underlying mechanism. We report that conditional MRTF-A deletion in cardiomyocytes attenuated Ang-II-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…It has also been shown that ablation of miR-155 in cardiomyocytes appears to be sufficient to blunt the hypertrophic response induced by phenoephrine (PE) ( Seok et al, 2014 ). This alternative model wherein MKL1 activates miR-155 transcription in cardiomyocytes to promote cardiac hypertrophy is certainly tempting in light of our recent report that cardiomyocyte-specific MKL1 deletion attenuates angiotensin II induced cardiac hypertrophy in mice ( Wu et al, 2020 ). Second, the finding that MKL1 relies on NF-κB to regulate miR-155 transcription reinforces the notion that MKL1 and NF-κB are functionally interconnected given previous investigations linking these two factors in the pathogenesis of atherosclerosis ( Fang et al, 2011 ), colitis ( Yu et al, 2014 ), and septic shock ( Yu et al, 2017 ), However, the precise role of NF-κB in the pathogenesis of cardiac hypertrophy has not been conclusively demonstrated especially in animal models likely due to the isoform-specific effects of NF-κB ( Gordon et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that ablation of miR-155 in cardiomyocytes appears to be sufficient to blunt the hypertrophic response induced by phenoephrine (PE) ( Seok et al, 2014 ). This alternative model wherein MKL1 activates miR-155 transcription in cardiomyocytes to promote cardiac hypertrophy is certainly tempting in light of our recent report that cardiomyocyte-specific MKL1 deletion attenuates angiotensin II induced cardiac hypertrophy in mice ( Wu et al, 2020 ). Second, the finding that MKL1 relies on NF-κB to regulate miR-155 transcription reinforces the notion that MKL1 and NF-κB are functionally interconnected given previous investigations linking these two factors in the pathogenesis of atherosclerosis ( Fang et al, 2011 ), colitis ( Yu et al, 2014 ), and septic shock ( Yu et al, 2017 ), However, the precise role of NF-κB in the pathogenesis of cardiac hypertrophy has not been conclusively demonstrated especially in animal models likely due to the isoform-specific effects of NF-κB ( Gordon et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin (ET-1) was purchased from Peprotech. CCG-1423 ( Chen et al, 2020a ; Wu et al, 2020 ) and PDTC ( Xu et al, 2017 ) were purchased from Selleck. MKL1 expression constructs and miR-155 promoter-luciferase constructs have been described previously ( Basso et al, 2012 ; Thompson et al, 2013 ; Li et al, 2019c ).…”
Section: Methodsmentioning
confidence: 99%
“…Transient transfections were performed with Lipofectamine 2000. Luciferase activities were assayed 24–48 h after transfection using a luciferase reporter assay system (Promega) as previously described ( Wu et al, 2020 ; Yang et al, 2020a,b ). For conditioned media (CM) collection, the cells were switched to and incubated with serum-free media overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were performed essentially as described before ( Chen et al, 2020a , b , c ; Dong et al, 2020 ; Fan et al, 2020 ; Li et al, 2020a , b , c ; Lv et al, 2020 ; Mao et al, 2020 ; Sun et al, 2020 ; Wu et al, 2020 ; Yang et al, 2020 ). In brief, chromatin in control and treated cells were cross-linked with 1% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%